Obesity in dyslipidemia and hypertension: A study among young adults of Delhi/NCR - Sumit Mishra; Benrithung Murry; N. Kiranmala Devi; Srishti Tripathi; Seyielenuo Suokhrie (Elsevier, 2023)
Aim: Obesity, dyslipidemia and hypertension contribute to cardiovascular risk. This study was conducted to evaluate the association of obesity with dyslipidemia and hypertension among young adults of Delhi/NCR. Materials and methods: This study was a cross-sectional study among young adults. Data on socio-demographic and lifestyle variables were collected using a pretested schedule. Anthropometric and physiological measurements were obtained using standard protocol to estimate obesity and hypertension. Biochemical assay was done using fasting blood samples. Logistic regression was employed to identify obesity variables associated with dyslipidemia and hypertension. Result: Almost 48.2% of the participants were either obese or overweight. Abdominal obesity was found to be relatively higher in terms of WHR (39.3%) followed by WHtR (33.8%) and WC (25.3%). Dyslipidemia in the form of TG was found to be the highest (23.3%) followed by low HDL (17.4%), high TC (8.4%) and high LDL (6.4%). Prevalence of hypertension was 23.3% Logistic regression analysis after controlling confounders revealed a significant association of generalized obesity with TC and TG, and WHtR showed a significant association with TC, TG, LDL and hypertension. Further, WC showed a significant association with LDL, HDL and hypertension. Conclusion: High WC and WHtR in young adults are associated with an increased risk for dyslipidemia and hypertension. Early detection of dyslipidemia and hypertension among college-going young adults would help in seeking timely intervention and reduce the burden of CVDs.